THE RELATIONSHIP OF PRIMARY PRODUCTIVITY OF PHYTOPLANKTON WITH OCEANOGRAPHIC PARAMETERS IN THE WATERS OF LUBUK GAUNG SUB-DISTRICT, SUNGAI SENIN DISTRICT, DUMAI - Sari, Tri Widia; Herlina, Nofripa; Badrun, Yeeri (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2023)
The waters of Lubuk Gaung Village, Sungai Sembilan District are areas that are widely used as transportation routes. Activities in these waters will cause environmental pollution, which affects the life of phytoplankton. The purpose of this study was to determine the relationship between the primary productivity of phytoplankton with oceanographic parameters in the waters of Lubuk Gaung Village, Sungai Sembilan District, Dumai. The method used is the survey method to determine the research station and the in situ method for measurement and sampling of oceanographic parameters. The results obtained are Oceanographic parameters from the three research stations, namely Brightness = 30 – 49 cm, Turbidity = 47.4 – 58.4 FTU, TSS = 124 – 209 mg/L, and BOD = 0.408 – 1.224 mg/L. The average value of primary productivity of the waters ranged from 48.07 to 79.69 mgC/m3/day. The value of primary productivity at station II is categorized into Oligotrophic, namely low waters. Stations I and III are categorized into mesotrophic waters, namely medium waters. The relationship between brightness, turbidity, and TSS with primary productivity has a very strong and positive (unidirectional) correlation value. The relationship between BOD and primary productivity has a very strong and negative (opposite) correlation.